PENGARUH CITRA MEREK, CITA RASA DAN MEDIA SOSIAL TERHADAP MINAT BELI PADA KONSUMEN JAGO COFEE - Leni Damayanti; Muhammad Ichwan Hamzah (JEBI | Jurnal Ekonomi Bisnis Indonesia, 2026)
The purpose of this research is to determine the influence of brand image, taste and social media variables on purchasing interest in Jago Cofee. The research method uses a quantitative qualitative approach. Based on the results of the discussion that has been obtained, the conclusions are as follows: Partial test results for the brand image variable have an effect on buying interest, the taste variable has an effect on buying interest and for social media it has no effect on buying interest. Simultaneous test results for brand image, taste and social media variables together (simultaneously) have a significant effect on the purchase interest variable with the results of the F test (simultaneous) obtaining F count > F table (19.999 > 2.76) and the significance value is more smaller than α of 0.05 or 0.000 < 0.05, then Ho is rejected and Ha is accepted. The Adjusted R Square (Adj. R2) is 0.471 or 47.1%, which means that the independent variables can explain changes in the purchase interest variable of 47.1% while the remaining 52.9% is explained by other factors outside the research.